Kronik hemiparezi hastalarında etkilenen ve sağlam taraf kalkaneal kemik mineral yoğunluğunun karşılaştırılması - (:unkn) unknown (My University, 2005)
İnme; motor kontrol kaybı, duyusal histe değişiklik, kognitif fonksiyonlarda ve konuşmada bozulma, dengesizlik veya koma gibi ani nörolojik defisitler ile sonuçlanan, beyin damarlarının tıkanması veya yırtılması sebebi ile travmatik olmayan bir beyin hasarıdır. Bu çalışmanın amacı kronik hemiparetik hastalarda hasta taraf ile normal taraf kalkaneal kemik mineral yoğunluğunun karşılaştırılmasıdır. Çalışmaya en az 3 ay önce inme geçirmiş, ünilateral hemiparezisi olup, bağımsız olarak mobilize olabilen 33 hemiparetik hasta dahil edildi. Genel durumu kötü, bilateral tutulumlu, doğumsal kalça çıkığı ve kalkaneusta kırık öyküsü olanlar çalışmaya alınmadı. Hastaların motor fonksiyonel seviyeleri, spastisite seviyeleri ve günlük yaşam aktivileri sırası ile Brunstrom, Ashworth ve Barthel İndeks’i skalaları ile değerlendirildi. Kalkaneal kemik mineral yoğunluğu (KMY) ise DXL-Calscan cihazı ile hem paretik hem de sağlam taraftan değerlendirildi. Hastaların yaş ortalamaları 58,9±11,9 yıl ve ortalama hastalık süreleri 20±19,4 ay idi. Hastaların %48,5’i erkek olup, %60,6’sı da sağ hemiparetik idi. Ashworth skalasına göre ortalama spastisite seviyeleri 1,6±1,2 olup, ortalama motor fonksiyonel seviye ve günlük yaşam aktiviteleri skoru sırası ile 4,4±1 ve 87,4±22,2 idi. Kalkaneal ortalama T skoru paratik tarafta –2,1±0,9; sağlam tarafta ise –1,7±0,7 idi. Pearson korelasyon analizine göre yaş ve paratik taraf Z skoru (r=0,42, p=0,01), Brunstrom skoru ile paretik taraf T skoru (r=0,48, p=0,005) ve Brunstrom skoru ile paretik taraf KMY değerleri (r=0,51, p=0,002) arasında pozitif korelasyon; yaş ile hastalık süresi (r= -0,36, p=0,03), Ashworth skoru ile Brunstrom skoru (r= -0,66, p=0,0001), Ashworth skoru ile paretik taraf T skoru (r= -0,41, p=0,01), Ashworth skoru ile paretik taraf Z skoru (r= -0,35, p=0,04) ve Ashworth skoru ile paretik taraf KMY değerleri (r= -0,46, p=0,01) arasında negatif korelasyon mevcuttu. Bununla birlikte, paretik taraf ile sağlam taraf kemik mineral yoğunluğu değerleri arasında istatistiksel olarak anlamlı bir fark tespit edilmedi.

Stroke is a non-traumatic brain injury caused by occlusion or rupture of cerebral blood vessels that results in sudden neurological deficit characterized by loss of motor control, altered sensation, cognitive or language impairment, disequilibrium, or coma. Immobilization is an important risk factor for osteoporosis. The aim of this study was to compare between affected and non-affected side’s calcaneal bone mineral density in chronic hemiparetic patients. Thirty-tree unilateral and independently mobile hemiparetic patients due to stroke were included in the study. The exclusion criteria were to have poor general health status, bilateral involvement, congenital dislocation of hip and past calcaneal fracture history. Motor functional level, spasticity and daily living activities of the patients were assessed by using Brunstrom, Ashworth and Barthel scales, respectively. The calcaneal bone mineral density was evaluated with DXL-Calscan in both affected and non-affected side of all patients. Patients’ mean age and duration of disease were 58.9±11.9 years and 20±19.4 months, respectively. 48.5% of patients were male and 60.6% has right side hemiparesis. Their mean spasticity level was 1.6±1.2 according to Ashworth Scale. Mean motor functional level and activity of daily living score were 4.5±1 and 87.4±22.2, respectively. The calcaneal mean T score was –2.1±0.9 and –1.7±0.7 in affected and non-affected side, respectively. In the pearson correlation analysis, there were positive correlation between age and non-affected Z score (r=0.42, p=0.01); Brunstrom score and affected side T score (r=0.48, p=0.005); Brunstrom score and affected side BMD (r=0.51, p=0.002). On the other hand, there were negative correlation between age and disease duration (r=-0.36, p=0.03); Ashworth score and Brunstrom (r=-0.66, p=0.0001), affected side T score (r=-0.41, p=0.01), affected side Z score (r=-0.35, p=0.04), affected BMD (r=-0.46, p=0.01). However, there was no significant difference between affected and non-affected side’s bone mineral density value according to independent t test. We found out that more spasticity level was lower BMD value was. As a result, spasticity and motor functional level may be determining factors for BMD value in hemiparetic patients.
The comparison between affected and non-affected side of the calcaneal bone density in chronic hemiparetic patients
Keywords: Tıbbi Araştırmalar Deneysel; Rehabilitasyon; Romatoloji